2019
DOI: 10.3390/nano10010051
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Structural, Thermal and Mechanical Properties of PLA/PHB/Cellulose Biodegradable Nanocomposites Obtained by Compression Molding, Extrusion, and 3D Printing

Abstract: Biodegradable blends and nanocomposites were produced from polylactic acid (PLA), poly(3-hydroxybutyrate) (PHB) and cellulose nanocrystals (NC) by a single step reactive blending process using dicumyl peroxide (DCP) as a cross-linking agent. With the aim of gaining more insight into the impact of processing methods upon the morphological, thermal and mechanical properties of these nanocomposites, three different processing techniques were employed: compression molding, extrusion, and 3D printing. The addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 51 publications
3
81
0
1
Order By: Relevance
“…Polylactide is more and more commonly used in the production of composites reinforced with lignocellulosic fillers of natural origin [34][35][36][37] as well as in the production of blends with different polymers characterized by a significantly higher recommended processing temperature [38][39][40] or in contrast those more susceptible to thermal degradation [41,42]. The most commonly used technology for manufacturing biopolymers and their composites at an industrial scale is co-rotating twin-screw extrusion, due to its high throughput and mixing efficiency [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Polylactide is more and more commonly used in the production of composites reinforced with lignocellulosic fillers of natural origin [34][35][36][37] as well as in the production of blends with different polymers characterized by a significantly higher recommended processing temperature [38][39][40] or in contrast those more susceptible to thermal degradation [41,42]. The most commonly used technology for manufacturing biopolymers and their composites at an industrial scale is co-rotating twin-screw extrusion, due to its high throughput and mixing efficiency [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 3,6-dimethyl-1,4-dioxane-2,5-dione as L-lactide monomer was surface grafted on CNF also was able to improve the homogeneity in the PLA matrix, and it was found that the crystallinity of the extruded filaments increased about 100% [ 89 ]. On the other hand, PLA, poly(3-hydroxybutyrate), and CNC crosslinked with dicumyl peroxide was investigated for its properties through various fabrication techniques, as shown in Figure 4 [ 90 ]. While the dicumyl peroxide addition improved the homogeneity of CNC in the polymer matrix and enhanced the interfacial adhesion between the polymers.…”
Section: Cellulose-based Polymers In 3d Printing Technologymentioning
confidence: 99%
“… Schematic representation of PLA/PHB blends and nanocomposites preparation and processing of films, filaments, and 3D-printed meshes [ 90 ]. …”
Section: Figurementioning
confidence: 99%
“…Bioplastics are already used in an increasing number of branches, e.g., packaging, catering products, agriculture, coatings and adhesives, toys, textiles, electronics, automotive, building and construction, medical applications, and many other sectors. Biopolymers PLA (poly(lactic acid)) and PHAs (polyhydroxyalkanoates) are generally well-researched and are the prime leaders of biopolymers production capacity growth [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%